BEBAN KERJA PENGARUHNYA TERHADAP KINERJA PEGAWAI SAAT PANDEMI COVID-19 DI DINAS KESEHATAN PROVINSI BENGKULU - Zulasmi Octarina; Veby Fransisca Rozi; Fadillah Sari (Avicenna: Jurnal Ilmiah, 2023)
Background: During the Covid-19 Pandemic, the Health Department is one of the stakeholders that handles COVID-19. Data on Covid-19 cases in Bengkulu Province as of December 2020 confirmed 3,733 cases (20.28%). This problem will directly make the work of official employees more difficult. The obstacle in the performance of employees at the Bengkulu Provincial Health Office is that employees are not maximal in providing services. Objectives: To analyze the workload on employee performance during the Covid-19 pandemic at the Bengkulu Provincial Health Office. Methods: This type of research is quantitative research to examine a particular population or sample, collect data, use research instruments with the aim of knowing the effect of the independent variable on the dependent variable. The population in this study were employees of the Bengkulu Province Health Office with a total sample of 76 people. The hypothesis test with the t test (Partial Significance). Results: The results showed that workload had a positive influence on employee performance and simultaneous testing of workload together had a positive effect on employee performance during a pandemic Covid-19 Bengkulu Provincial Health Office. It is recommended as a consideration in paying attention to the needs of employees, especially on the workload of employees so that they can improve employee performance better.   Keywords: Workload, Covid-19, Performance